Analisis Postur Kerja Analis Laboratorium dengan Metode RULA untuk Mengurangi Risiko MSDs - Febri Gilang Arjuna; Uun Novalia Harahap; Yetti Meuthia Hasibuan; Haniza Haniza (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to analyze the working postures of laboratory analysts using the Rapid Upper Limb Assessment (RULA) method to identify the risk of Musculoskeletal Disorders (MSDs). Observations were conducted during primary laboratory activities to document body posture, joint angles, and work duration. The RULA assessment indicated moderate to high risk, suggesting the need for immediate corrective actions. Major contributing factors to MSD risk included bent working postures, repetitive arm movements, and non-ergonomic workstation design. Recommended improvements involve workstation adjustment, posture correction, and the application of ergonomic principles. This study is expected to support MSD prevention efforts and improve comfort and productivity among laboratory analysts.